O12.5 Partner notification outcomes for chlamydia/gonorrhea cases diagnosed through clinics vs getcheckedonline in british columbia. (14th July 2019) - Zamanpour, Arina; Wong, Jason; Haag, Devon; Grennan, Troy; Hoyano, Dee; Bannar-Martin, Sophie; Mema, Silvina; Karlsson, Maja; Fairley, Christopher; Ogilvie, Gina; Gilbert, Mark
Abstract : Background: GetCheckedOnline (GCO) is an internet-based testing service for sexually transmitted and blood-borne infections in British Columbia (BC), Canada that is highly accepted by clients. The literature has not addressed whether treatment and partner notification (PN) outcomes differ between clients of internet-based testing services and clinic-based clients. We sought to compare treatment uptake, engagement in PN, and PN outcomes between chlamydia (CT) and/or gonorrhea (GC) cases diagnosed through GCO and two provincially-operated sexually transmitted infection clinics. Methods: A matched case-control study was conducted among CT/GC cases in BC from 2016–2018. All cases diagnosed through GCO were selected and matched to two clinic cases (controls) based on diagnosis, gender, age group, and specimen collection date. Using a cascade of care, PN outcomes were compared between partners of GCO and clinic cases. Bivariate comparisons were conducted using chi-square or Fisher's exact test. Results: There were 257 GCO cases matched to 514 clinic cases. Treatment uptake did not differ between GCO (254/257, 98.9%) and clinic (513/514, 99.8%) cases. There was no difference in the proportion of notified partners between GCO (176/287, 61.3%) and clinic cases (338/520, 65.0%) although a greater proportion (P<0.01) of notifiable partners reported by clinic cases were notified by public health (44/520, 8.5%) vs. GCO cases (6/287, 2.1%). Among all notified partners, clinic cases reported a greater proportion (P<0.01) of tested partners (114/338, 33.7%) than did GCO cases (38/176, 21.6%). Of all notifiable partners, positivity was higher (P<0.01) among clinic cases (93/520, 17.9%) than GCO cases (29/287, 10.1%). Conclusion: GCO clients diagnosed with CT or GC demonstrated similar treatment uptake and engagement in PN to clinic clients. The difference in partner testing may be due to different populations being reached by internet-based testing and merits further investigation. The high positivity rate among partners underscores the importance of PN. Disclosure: No significant relationships.